Production of Crops with Organic Amendments in mountain agro ecosystem in Uttarakhand - Aswal, J. S.; Negi, D. S.; Sha, Binita; Uniyal, D. P. (Indian Farming, 2016)
Emphasis is currently being laid on use of renewable sources in agriculture with a view to minimize the synthetic chemical inputs and curtailing down the environmental pollution. Organic sources offer a key strategy against negative consequences of excess use of inorganic sources in agriculture fields and discharge of soil wastes into the open environment. The degradable solid waste material conversion into organic compost using organic sources becomes a product to sustain the agricultural and environmental quality.